Atypical CT and MR imaging of insulinoma: A case report - Sahat Matondang; Benedicta Mutiara Suwita; Taufik Budianto; Ening Krisnuhoni (Journal of Clinical and Translational Endocrinology Case Reports, 2021)
Insulinoma is a rare endocrine tumor that causes hypoglycemia, with incidence of only 1–4 cases per 1 million population. Various clinical manifestations of hypoglycemia may resemble neurological, psychiatric and cardiac problems, which result in diagnosis delay. In this case, we reported a 30-year-old woman experiencing deterioration of consciousness and history of repeated seizures, despite normal EEG, brain CT and MRI. Multiphase contrast-enhanced abdominal CT showed hypovascular nodule, which is not typical for insulinoma. Multiphase contrast-enhanced MRI showed hypointense T1WI, hyperintense T2WI pancreatic nodule which enhance in arterial phase. Laboratory and histopathological examination confirm the diagnosis of neuroendocrine tumor. We described the atypical clinical manifestations, as well as atypical imaging appearance of pancreatic insulinoma in this patient. Lesion characteristics and its differential diagnosis based on CT and MRI were discussed, with several features to help differentiating pancreatic insulinoma from adenocarcinoma in accordance with the current literature.